Comparative study between dexmedetomidine and dexamethasone as an adjuvant to levobupivacaine for supraclavicular brachial plexus block in patients undergoing upper limb surgeries - Suman Sarkar; Debarati Goswami; Sujan Sarkar; Sandesh Rathod (Asian Journal of Medical Sciences, 2023)
Background: Brachial plexus block (BPB) is widely used nowadays in patients undergoing upper limb surgery. Levobupivacaine is one of the best local anesthetics in the current scenario in this field. Both dexmedetomidine (DM) and dexamethasone (DX) are commonly used local anesthetic adjuvants in BPB to enhance blocking effects. In anesthesiology, there is always a search for a better alternative. Aims and Objectives: In this study, we investigated the effect of DM and DX as adjuvants to levobupivacaine on the quality of supraclavicular BPB. Materials and Methods: A prospective, double-blind, randomized controlled intervention study (superiority trial) was done involving 60 patients aged 20–60 years, randomly allocated into two equal groups (group S-DM group-Patients were received Injection 0.25% Levobupivacaine 2 mg/kg body weight+Inj. DM 1 mcg/kg body weight+distilled water [total volume 30 mL] and group C-DX group-Patients received Inj. 0.25% Levobupivacaine 2 mg/kg+Inj. DX 0.1 mg/kg body weight+Distilled water [total volume 30 mL]). The scores of the modified Gormley and Hill scale and the modified Bromage scale were recorded along with hemodynamic parameters. Pearson’s Chi-square test, Mann-Whitney U-test, one-way ANOVA, Kaplan–Meier survival analysis, and Z-test were used for statistical analysis. Results: The onset of motor block was shorter in group-S patients (14.2667±1.0807 [min]) compared to group-C (15.9333±1.5742 [min]), and the duration of motor block was higher in group-S (708.5667±4.2644 [min]) compared to group-C patients (682.3667±20.0095 [min]) (P<0.001). Conclusion: DM is a better alternative to DX when added to levobupivacaine for decreasing the onset of sensory and motor block and increasing the duration of supraclavicular BPB.